Silver paste for manufacturing printed antenna

By optimizing the composition and proportion of silver paste, the shortcomings of existing silver paste in terms of conductivity, wear resistance and adhesion are solved, and efficient printing antenna manufacturing is achieved, which is suitable for a variety of application needs of electronic equipment.

CN119487584APending Publication Date: 2025-02-18HENKEL KGAA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280097599.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-06-30
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing silver paste used for printing antennas has shortcomings in electrical conductivity, wear resistance and adhesion, especially in aging tests that are prone to layering problems.

Method used

Provide a silver paste comprising an epoxy resin, a curing agent, a filler mixture (including silver sheets and silver balls), a diluent or curing accelerator, and a coupling agent. By optimizing the proportion and combination of these components, the conductivity of the silver paste is enhanced. properties, wear resistance and adhesiveness.

Benefits of technology

It realizes the effect of low resistance, high adhesion and good aging characteristics of silver paste in electronic equipment, or high wear resistance, low resistance, high strength and no bubbles, and solves the effect of existing silver paste in printing antenna manufacturing. Multiple defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005214031240000061
    Figure BDA0005214031240000061
  • Figure BDA0005214031240000071
    Figure BDA0005214031240000071
  • Figure BDA0005214031240000081
    Figure BDA0005214031240000081
Patent Text Reader

Abstract

The present invention provides a silver paste for manufacturing a printed antenna, a kit of parts for manufacturing a printed antenna for an electronic device comprising three of the silver pastes, the use of the silver paste as a via filling ink, a method for manufacturing a printed antenna circuit using the three of the silver pastes, a printed antenna for an electronic device obtained using the silver paste, and a method for manufacturing a printed antenna for an electronic device using the printed antenna. And an electronic device including the printed antenna. The silver paste comprises: 2 to 40 wt% of at least one epoxy resin; 0 to 5% by weight of at least one curing agent selected from the group consisting of amino resins, low temperature cationic curing agents, amine or imidazole capsule curing agents, and combinations thereof; 40 to 90 wt% of at least one filler mixture comprising silver flakes and silver balls; 10 to 25% by weight of at least one diluent, or 0 to 20% by weight of at least one curing accelerator; and 0 to 5 wt% of at least one coupling agent selected from the group consisting of silane coupling agents, titanium-based coupling agents, aluminum-based coupling agents, and combinations thereof, where all the above weight percentages are based on the total weight of the silver paste. The silver paste provided by the invention has high reliability and high conductivity, and has good weather resistance, or good wear resistance, or no bubble; and the combination of the three silver pastes can be excellently used for manufacturing a printed antenna.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a silver paste for manufacturing a printed antenna. In particular, the present invention provides a silver paste for manufacturing a printed antenna, a kit-of-parts for preparing a printed antenna for an electronic device comprising three of the silver pastes, use of the silver paste as a via fill ink, a method for preparing a printed antenna circuit using the three silver pastes, a printed antenna for an electronic device obtained using the silver paste, and an electronic device comprising the printed antenna. Background Art

[0002] As 5G communication technology enters our lives, there are more and more antennas in smartphones and other smart devices. Traditional LDS and FPC technologies can no longer meet the new requirements of antennas. According to the needs of the times, a new technology PDS (Printed Direct-forming Structure) has been developed. In PDS antennas, three types of silver paste (surface conductive ink, touch point conductive ink, and through-hole filling conductive ink) are required to provide good conductivity and good RF performance for the antenna.

[0003] As for surface conductive ink, existing surface conductive ink generally has high resistance and poor aging characteristics. As for touch point conductive ink, existing touch point conductive ink generally has high resistance and low wear resistance. As for through-hole filling conductive ink, existing through-hole filling conductive ink generally has low adhesive strength and bubbles. In addition, when surface conductive ink, touch point conductive ink and through-hole filling conductive ink are used in one application, mismatch usually occurs between them; and this mismatch causes many delamination problems during aging tests.

[0004] In view of the above, it is desirable to provide silver pastes for manufacturing printed antennas, especially those that can be used as surface conductive inks, touch point conductive inks, or through-hole filling conductive inks, which can overcome at least one of the above disadvantages in the prior art. In addition, it is desirable to provide a combination of three silver pastes, wherein the three silver pastes can be used as surface conductive inks, touch point conductive inks, or through-hole filling conductive inks, respectively, and the combination can be excellently used for manufacturing printed antennas. Summary of the invention

[0005] In a first aspect, the present invention provides a silver paste for making a printed antenna, comprising:

[0006] 2 to 40 wt. % of at least one epoxy resin;

[0007] 0 to 5 weight percent of at least one curing agent selected from amino resins, low temperature cationic curing agents, amine or imidazole capsule curing agents, and combinations thereof;

[0008] 40 to 90 weight percent of at least one filler mixture comprising silver flakes and silver spheres;

[0009] 10 to 25 wt % of at least one diluent, or 0 to 20 wt % of at least one curing accelerator; and

[0010] 0 to 5 weight percent of at least one coupling agent selected from the group consisting of silane coupling agents, titanium-based coupling agents, aluminum-based coupling agents, and combinations thereof,

[0011] All the above weight percentages are based on the total weight of the silver paste.

[0012] In particular, in a preferred embodiment of this aspect (hereinafter referred to as the "first embodiment"), the present invention provides a silver paste comprising:

[0013] 2 to 20% by weight, preferably 2 to 8% by weight, more preferably 4 to 6% by weight, of at least one epoxy resin,

[0014] 0 to 5 wt %, preferably 0.1 to 3 wt %, more preferably 0.2 to 2 wt % of at least one curing agent comprising an amino resin,

[0015] 40 to 90 wt. %, preferably 50 to 85 wt. %, more preferably 70 to 80 wt. % of at least one filler mixture, the filler mixture comprising 1 to 40 wt. % of a tap density of more than 2 to 7 g / cm 3 Silver flakes, 35 to 88% by weight, with a tap density of 5 to 7 g / cm 3 of silver balls, and 0.08 to 0.45 wt. % of zirconium hydroxide,

[0016] 5 to 25% by weight, preferably 10 to 23% by weight, more preferably 15 to 20% by weight of at least one diluent,

[0017] 0 to 5 wt %, preferably 0.3 to 3 wt %, more preferably 1.0 to 2.0 wt % of at least one coupling agent selected from silane coupling agents, titanium-based coupling agents, aluminum-based coupling agents, and combinations thereof,

[0018] All the above weight percentages are based on the total weight of the silver paste.

[0019] In another preferred embodiment of this aspect (hereinafter referred to as the "second embodiment"), the present invention provides a silver paste comprising:

[0020] 2 to 20% by weight, preferably 2 to 8% by weight, more preferably 4 to 6% by weight, of at least one epoxy resin,

[0021] 0.1 to 5 wt %, preferably 0.1 to 3 wt %, more preferably 0.2 to 2 wt % of at least one curing agent comprising an amino resin,

[0022] 40 to 90 wt. %, preferably 50 to 85 wt. %, more preferably 70 to 80 wt. % of at least one filler mixture, the filler mixture comprising 1 to 30 wt. % of a tap density of more than 2 to 7 g / cm 3 Silver flakes, 25 to 75% by weight, with a tap density of 5 to 7 g / cm 3 silver balls, 10 to 40% by weight of wear-resistant powder having a particle size of 3.5 to 10 μm, and 0.08 to 0.45% by weight of zirconium hydroxide,

[0023] 5 to 25% by weight, preferably 10 to 23% by weight, more preferably 15 to 20% by weight of at least one diluent,

[0024] 0 to 5 wt %, preferably 0.3 to 3 wt %, more preferably 1.0 to 2.0 wt % of at least one coupling agent selected from silane coupling agents, titanium-based coupling agents, aluminum-based coupling agents, and combinations thereof,

[0025] All the above weight percentages are based on the total weight of the silver paste.

[0026] In yet another preferred embodiment of this aspect (hereinafter referred to as the "third embodiment"), the present invention provides a silver paste comprising:

[0027] 10 to 40% by weight, preferably 11 to 30% by weight, more preferably 12 to 20% by weight of at least one epoxy resin,

[0028] 0.1 to 3 wt %, preferably 0.2 to 2 wt %, more preferably 0.3 to 1 wt % of at least one curing agent, the curing agent comprising a low temperature cationic curing agent, or an amine or imidazole capsule curing agent,

[0029] 50 to 90 wt. %, preferably 60 to 88 wt. %, more preferably 75 to 85 wt. % of at least one filler mixture, the filler mixture comprising 45 to 89 wt. % of a tap density of more than 2 to 7 g / cm 3 Silver flakes, and 1 to 45 wt % of a tap density of 5 to 7 g / cm 3 The silver ball,

[0030] 1 to 20% by weight, preferably 2 to 15% by weight, more preferably 3 to 10% by weight of at least one curing accelerator,

[0031] 0 to 5 wt %, preferably 0.3 to 3 wt %, more preferably 1.0 to 2.0 wt % of at least one coupling agent selected from silane coupling agents, titanium-based coupling agents, aluminum-based coupling agents, and combinations thereof,

[0032] All the above weight percentages are based on the total weight of the silver paste.

[0033] In a second aspect, the present invention provides a kit of parts for preparing a printed antenna for an electronic device, comprising individually packaged

[0034] a first container containing a silver paste according to the first embodiment,

[0035] a second container containing a silver paste according to the second embodiment, and

[0036] - A third container containing the silver paste according to the third embodiment.

[0037] In a third aspect, the present invention provides use of the silver paste according to the third embodiment as a via filling ink for conductive connection between a surface silver paste and a touch point silver paste.

[0038] In a fourth aspect, the present invention provides a method of making a printed antenna circuit using the silver paste according to the first embodiment, the silver paste according to the second embodiment, and the silver paste according to the third embodiment.

[0039] In a fifth aspect, the present invention provides a printed antenna for electronic devices obtained using the silver paste according to the present invention.

[0040] In a sixth aspect, the present invention provides an electronic device comprising a printed antenna according to the present invention.

[0041] The silver paste according to the present invention can provide very low resistance (with a sheet resistance of less than 10mohm / square), high adhesion, and good aging characteristics; or the silver paste according to the present invention can provide high wear resistance up to 3000 cycles, and low resistance; or the silver paste according to the present invention can provide high strength and no bubbles. The kit of parts for preparing printed antennas for electronic devices according to the present invention does not have mismatching problems. DETAILED DESCRIPTION

[0042] Those of ordinary skill in the art will appreciate that this discussion is merely a description of an exemplary embodiment and is not intended to limit the broader aspects of the invention. Unless otherwise expressly indicated, each aspect so described may be combined with any one or more other aspects. In particular, any feature indicated as being preferred or advantageous may be combined with any one or more other features indicated as being preferred or advantageous.

[0043] Unless otherwise specified, in the context of the present invention, the terms used should be interpreted according to the following definitions.

[0044] As used herein, the singular forms "a," "an," "said," and "the" include both singular and plural referents unless otherwise specified.

[0045] As used herein, the terms "comprising" and "containing" are synonymous with "including" or "comprising", are inclusive or open-ended, and do not exclude additional, unrecited members, elements, or method steps.

[0046] The term "at least one" used herein to define a component refers to the type of the component, rather than the absolute number of molecules. For example, "at least one epoxy resin" refers to one type of epoxy resin or a mixture of multiple different epoxy resins.

[0047] All tap density data used herein are determined according to ISO 3953:1993. The principle of the specified method is to tap a specified amount of powder in a container by means of a tapping instrument until the volume of the powder no longer decreases. The mass of the powder divided by its volume after the test gives its tap density.

[0048] All particle size data used herein refer to "D50 particle size", which represents the median diameter in a volume-based particle size distribution curve obtained by measuring with a laser diffraction particle size analyzer. In this technique, the size of particles in a suspension or emulsion is measured using the diffraction of a laser beam based on the application of Frauhofer or Mie theory. In the present invention, the Mie theory or the modified Mie theory for non-spherical particles is applied, and the average particle size or D50 value involves scattering measurements at an angle of 0.02 to 135 degrees relative to the incident laser beam.

[0049] Unless otherwise specified, recitations of numerical endpoints include all numbers and fractions subsumed within the corresponding range, as well as the recited endpoint.

[0050] Unless otherwise defined, all terms (including technical and scientific terms) used in disclosing the present invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.

[0051] In one aspect, the present disclosure is generally directed to a silver paste for making a printed antenna, comprising:

[0052] 2 to 40 wt. % of at least one epoxy resin;

[0053] 0 to 5 weight percent of at least one curing agent selected from amino resins, low temperature cationic curing agents, amine or imidazole capsule curing agents, and combinations thereof;

[0054] 40 to 90 weight percent of at least one filler mixture comprising silver flakes and silver spheres;

[0055] 10 to 25 wt % of at least one diluent, or 0 to 20 wt % of at least one curing accelerator; and

[0056] 0 to 5 weight percent of at least one coupling agent selected from the group consisting of silane coupling agents, titanium-based coupling agents, aluminum-based coupling agents, and combinations thereof,

[0057] All the above weight percentages are based on the total weight of the silver paste.

[0058] First embodiment

[0059] In a first embodiment of the present invention, the silver paste comprises:

[0060] 2 to 20% by weight, preferably 2 to 8% by weight, more preferably 4 to 6% by weight, of at least one epoxy resin,

[0061] 0 to 5 wt %, preferably 0.1 to 3 wt %, more preferably 0.2 to 2 wt % of at least one curing agent comprising an amino resin,

[0062] 40 to 90 wt. %, preferably 50 to 85 wt. %, more preferably 70 to 80 wt. % of at least one filler mixture, the filler mixture comprising 1 to 40 wt. % of a tap density of more than 2 to 7 g / cm 3 Silver flakes, 35 to 88% by weight, with a tap density of 5 to 7 g / cm 3 of silver balls, and 0.08 to 0.45 wt. % of zirconium hydroxide,

[0063] 5 to 25% by weight, preferably 10 to 23% by weight, more preferably 15 to 20% by weight of at least one diluent,

[0064] 0 to 5 wt %, preferably 0.3 to 3 wt %, more preferably 1.0 to 2.0 wt % of at least one coupling agent selected from silane coupling agents, titanium-based coupling agents, aluminum-based coupling agents, and combinations thereof,

[0065] All the above weight percentages are based on the total weight of the silver paste.

[0066] In the first embodiment of the present invention, preferably, the epoxy resin is selected from bisphenol-A resin, bisphenol-F resin and alicyclic epoxy resin; preferably selected from bisphenol-A resin and bisphenol-F resin; and more preferably bisphenol-A resin.

[0067] Alternatively or additionally, in the first embodiment of the present invention, preferably, the amino resin is catalyzed by benzenesulfonic acid, wherein the amino resin is preferably selected from urea formaldehyde resin, melamine formaldehyde resin, and polyamide polyamine epichlorohydrin, more preferably selected from melamine formaldehyde resin; and / or the benzenesulfonic acid is used in the form of pyridinium p-toluenesulfonate.

[0068] Alternatively or additionally, in the first embodiment of the present invention, preferably, based on the total weight of the silver paste, the filler mixture comprises 2 to 35 wt. %, preferably 10 to 30 wt. %, more preferably 12 to 20 wt. % of silver flakes; and / or based on the total weight of the silver paste, the filler mixture comprises 40 to 80 wt. %, preferably 50 to 70 wt. %, more preferably 55 to 65 wt. % of silver spheres; and / or based on the total weight of the silver paste, the filler mixture comprises 0.1 to 0.3 wt. %, preferably 0.15 to 0.25 wt. % of zirconium hydroxide; and / or the particle size of the silver flakes is 5 to 8 μm; and / or the silver flakes have a particle size of 3 to 6 g / cm 3 The tap density is preferably 3.5 to 5 g / cm 3 and / or the silver spheres have a particle size of 0.2 to 5 μm, preferably a particle size of 0.5 to 2 μm; and / or the silver spheres have a tap density of 5.5 to 6.5 g / cm 3 .

[0069] Alternatively or additionally, in the first embodiment of the invention, preferably, the diluent is selected from ketones and esters; preferably selected from isophorone, acetylacetone, cyclohexyl acetate, ethylene glycol butyl ether acetate, and propylene glycol methyl ether acetate; and is a mixture of isophorone, acetylacetone, cyclohexyl acetate, ethylene glycol butyl ether acetate, and propylene glycol methyl ether acetate.

[0070] The silver paste according to the first embodiment can provide very low resistance (having a sheet resistance of less than 10 mohm / square), high adhesion, and good aging characteristics; therefore, can be successfully used as a surface conductive ink.

[0071] Second embodiment

[0072] In a second embodiment of the present invention, the silver paste comprises:

[0073] 2 to 20% by weight, preferably 2 to 8% by weight, more preferably 4 to 6% by weight, of at least one epoxy resin,

[0074] 0.1 to 5 wt %, preferably 0.1 to 3 wt %, more preferably 0.2 to 2 wt % of at least one curing agent comprising an amino resin,

[0075] 40 to 90 wt. %, preferably 50 to 85 wt. %, more preferably 70 to 80 wt. % of at least one filler mixture, the filler mixture comprising 1 to 30 wt. % of a tap density of more than 2 to 7 g / cm 3 Silver flakes, 25 to 75% by weight, with a tap density of 5 to 7 g / cm 3 silver balls, 10 to 40% by weight of wear-resistant powder having a particle size of 3.5 to 10 μm, and 0.08 to 0.45% by weight of zirconium hydroxide,

[0076] 5 to 25% by weight, preferably 10 to 23% by weight, more preferably 15 to 20% by weight of at least one diluent,

[0077] 0 to 5 wt %, preferably 0.3 to 3 wt %, more preferably 1.0 to 2.0 wt % of at least one coupling agent selected from silane coupling agents, titanium-based coupling agents, aluminum-based coupling agents, and combinations thereof,

[0078] All the above weight percentages are based on the total weight of the silver paste.

[0079] In the second embodiment of the present invention, preferably, the epoxy resin is selected from bisphenol-A resin, bisphenol-F resin and alicyclic epoxy resin; preferably selected from bisphenol-A resin and bisphenol-F resin; and more preferably bisphenol-A resin.

[0080] Alternatively or additionally, in a second embodiment of the invention, preferably, the amino resin is catalyzed by benzenesulfonic acid, wherein the amino resin is preferably selected from urea formaldehyde resin, melamine formaldehyde resin, and polyamide polyamine epichlorohydrin, more preferably selected from melamine formaldehyde resin; and / or the benzenesulfonic acid is used in the form of pyridinium p-toluenesulfonate.

[0081] Alternatively or additionally, in a second embodiment of the present invention, preferably, based on the total weight of the silver paste, the filler mixture contains 2 to 25 weight %, preferably 3 to 10 weight %, more preferably 4 to 8 weight % of silver flakes; and / or based on the total weight of the silver paste, the filler mixture contains 30 to 70 weight %, preferably 40 to 60 weight %, more preferably 45 to 55 weight % of silver balls; and / or based on the total weight of the silver paste, the filler mixture contains 12 to 30 weight %, preferably 18 to 25 weight % of wear-resistant powder; and / or based on the total weight of the silver paste, the filler mixture contains 0.1 to 0.3 weight %, preferably 0.15 to 0.25 weight % of zirconium hydroxide.

[0082] Alternatively or additionally, in the second embodiment of the present invention, preferably, the silver flakes have a particle size of 5 to 8 μm; and / or the silver flakes have a particle size of 3 to 6 g / cm 3 The tap density is preferably 3.5 to 5 g / cm 3 and / or the silver spheres have a particle size of 0.2 to 5 μm, preferably a particle size of 0.5 to 2 μm; and / or the silver spheres have a tap density of 5.5 to 6.5 g / cm 3 ; and / or the wear-resistant powder is selected from silicon powder, zirconium oxide powder, aluminum oxide powder and alloy powder, wherein the alloy powder is preferably selected from iron-nickel alloy powder and iron-manganese alloy powder, more preferably iron-nickel alloy powder; and / or the particle size of the alloy powder is 4 to 8 μm, preferably 4.5 to 7 μm.

[0083] Alternatively or additionally, in the second embodiment of the invention, preferably, the diluent is selected from ketones and esters; preferably selected from isophorone, acetylacetone, cyclohexyl acetate, ethylene glycol butyl ether acetate, and propylene glycol methyl ether acetate; and is a mixture of isophorone, acetylacetone, cyclohexyl acetate, ethylene glycol butyl ether acetate, and propylene glycol methyl ether acetate.

[0084] The silver paste according to the second embodiment can provide high wear resistance (2000 to 3000 cycles), and relatively low resistance; therefore, it can be successfully used as a touch point conductive ink.

[0085] Third embodiment

[0086] In a third embodiment of the present invention, the silver paste comprises:

[0087] 10 to 40% by weight, preferably 11 to 30% by weight, more preferably 12 to 20% by weight of at least one epoxy resin,

[0088] 0.1 to 3 wt %, preferably 0.2 to 2 wt %, more preferably 0.3 to 1 wt % of at least one curing agent, the curing agent comprising a low temperature cationic curing agent, or an amine or imidazole capsule curing agent,

[0089] 50 to 90 wt. %, preferably 60 to 88 wt. %, more preferably 75 to 85 wt. % of at least one filler mixture, the filler mixture comprising 45 to 89 wt. % of a tap density of more than 2 to 7 g / cm 3 Silver flakes, and 1 to 45 wt % of a tap density of 5 to 7 g / cm 3 The silver ball,

[0090] 1 to 20% by weight, preferably 2 to 15% by weight, more preferably 3 to 10% by weight of at least one curing accelerator,

[0091] 0 to 5 wt %, preferably 0.3 to 3 wt %, more preferably 1.0 to 2.0 wt % of at least one coupling agent selected from silane coupling agents, titanium-based coupling agents, aluminum-based coupling agents, and combinations thereof,

[0092] All the above weight percentages are based on the total weight of the silver paste.

[0093] In the third embodiment of the present invention, preferably, the epoxy resin is selected from bisphenol-A resin, bisphenol-F resin and alicyclic epoxy resin; preferably selected from bisphenol-F resin and alicyclic epoxy resin; and more preferably a combination of bisphenol-F resin and alicyclic epoxy resin.

[0094] Alternatively or additionally, in the third embodiment of the invention, preferably, the low temperature cationic curing agent is cured at a temperature of 60 to 90°C, preferably at a temperature of 70 to 80°C; and / or the low temperature cationic curing agent is hexafluoroantimonate and / or hexafluorophosphate, and preferably hexafluoroantimonate; and / or the amine or imidazole capsule curing agent is an imidazole capsule curing agent.

[0095] Alternatively or additionally, in a third embodiment of the present invention, preferably, based on the total weight of the silver paste, the filler mixture comprises 50 to 85 wt%, preferably 60 to 80 wt%, more preferably 65 to 75 wt% of silver flakes; and / or based on the total weight of the silver paste, the filler mixture comprises 2 to 35 wt%, preferably 5 to 20 wt%, more preferably 8 to 15 wt% of silver spheres; and / or the particle size of the silver flakes is 5 to 20 μm; and / or the particle size of the silver spheres is 5 to 20 μm; and / or the silver flakes have a particle size of 3 to 6 g / cm 3 The tap density is preferably 3.5 to 5 g / cm 3 and / or the tap density of the silver sphere is 5.5 to 6.5 g / cm 3 .

[0096] Alternatively or additionally, in the third embodiment of the present invention, preferably, the curing accelerator is selected from oxetanes, and preferably is (3-ethyl-3-oxetanyl)methanol.

[0097] The silver paste according to the third embodiment can provide high strength and has no bubbles; therefore, can be successfully used as a via-filling conductive ink.

[0098] The method for preparing the silver paste according to the present invention may be any conventional method for preparing silver paste, and is not particularly limited as long as such silver paste can be obtained. For example, the method for preparing the silver paste may include: stirring at least one epoxy resin and optionally at least one diluent, adding at least one filler mixture and stirring the mixture thus obtained, adding optionally at least one curing agent and at least one coupling agent and stirring the mixture thus obtained, and then subjecting the mixture obtained above to triple-roll grinding.

[0099] In another aspect, the present disclosure relates to a kit of parts for preparing a printed antenna for an electronic device, comprising individually packaged

[0100] a first container containing a silver paste according to the first embodiment,

[0101] a second container containing a silver paste according to the second embodiment, and

[0102] - A third container containing the silver paste according to the third embodiment.

[0103] The combination of the three silver pastes has no mismatch problem and has good aging characteristics.

[0104] In yet another aspect, the present disclosure relates to the use of the silver paste according to the third embodiment as a through-hole filling ink for a conductive connection between a surface silver paste and a touch point silver paste, wherein the conductive connection is preferably a conductive connection between the silver paste according to the first embodiment and the silver paste according to the second embodiment.

[0105] In yet another aspect, the present disclosure relates to a method for preparing a printed antenna circuit, comprising the steps of:

[0106] i) applying the silver paste according to the third embodiment to the through-hole in the middle frame of the mobile phone with a glue dispenser, and then curing it at 80 to 90° C. for 0.5 to 2 hours, preferably 0.8 to 1.5 hours, more preferably about 1 hour, and leaving it for 0.5 to 2 hours to obtain a product;

[0107] ii) applying the silver paste according to the first embodiment to the product obtained in step i) three times with a pad printer, and then curing it at 80 to 90° C. for 0.5 to 2 hours, preferably 0.8 to 1.5 hours, more preferably about 1 hour, to obtain an Ag film with a thickness of 10 to 20 μm, preferably about 15 μm; and

[0108] iii) applying the silver paste according to the second embodiment to the Ag film obtained in step ii) five times with a pad printer, and curing it at 80 to 90° C. for 1 to 3 hours, preferably 1.5 to 2.5 hours, more preferably about 2 hours to obtain a printed antenna circuit.

[0109] Preferably, the middle frame of the mobile phone is made of PC, LPA, aluminum alloy, ceramic, glass and / or magnesium alloy.

[0110] In yet another aspect, the present invention also provides a printed antenna for an electronic device, which is obtained using the silver paste according to the present invention, preferably using the silver paste according to the first embodiment, the silver paste according to the second embodiment, and / or the silver paste according to the third embodiment, and more preferably using the set of components according to the present invention.

[0111] In yet another aspect, the present invention provides an electronic device comprising a printed antenna according to the present invention.

[0112] With regard to other preferred embodiments of the kit of parts, the use of the silver paste according to the third embodiment, the method for preparing a printed antenna circuit, the printed antenna for an electronic device, and the electronic device comprising the printed antenna, what has been said about the silver paste applies mutatis mutandis.

[0113] Example

[0114] The present invention is further described in detail and illustrated in conjunction with the following examples. These examples are intended to help those skilled in the art better understand and practice the present invention, but are not intended to limit the scope of the present invention. Unless otherwise stated, all amounts in the examples are based on weight in grams.

[0115] Material

[0116] The following materials were used in the examples:

[0117]

[0118]

[0119] Preparation of silver paste

[0120] The silver paste according to the examples (hereinafter referred to as "EX") and comparative examples (hereinafter referred to as "CE") of the present invention is prepared according to the composition described in Table 1 as follows: one or more epoxy resins and an optional diluent are stirred until uniform; a filler mixture is added and the mixture thus obtained is stirred until uniform; an optional curing agent or curing accelerator is added and the mixture thus obtained is stirred until uniform; and the mixture obtained above is then subjected to triple-roll grinding.

[0121] Test Method

[0122] The properties of the silver pastes of Examples and Comparative Examples were measured according to the following methods.

[0123] Sheet resistance of silver paste

[0124] The silver paste of the examples and comparative examples was coated onto a Mylar substrate with a gap of 2 mil. The samples were cured at 80 to 90°C for 1 hour. The 2-point probe measurement was performed as follows: A line about 100 mm long and about 2 mm wide was cut in the film for testing. The resistance was measured with a multimeter. The thickness of the line coating was measured at several locations on the line, and the average thickness was calculated. The sheet resistance is given by the following formula:

[0125] Sheet resistance [Ω / square / mil] = resistance [Ω] * thickness [mils] / square number [dimensionless]

[0126] Where, square number = length [mm] / width [mm]

[0127] The sheet resistance is specific to the silver paste when cured. The smaller the sheet resistance value, the better the conductivity. The silver paste of the first embodiment is acceptable with a sheet resistance of less than 10 mohm / square; the silver paste of the second embodiment is acceptable with a sheet resistance of no more than 30 mohm / square; and the silver paste of the third embodiment is acceptable with a sheet resistance of less than 80 mohm / square.

[0128] Adhesion of silver paste

[0129] The adhesion of silver paste is tested as follows: 1) Use a sharp blade to draw a specified area of ​​10 x 10 1mm*1mm, where each line must penetrate the ink to the end of the material; 2) Brush the surface with a dust-free cloth or brush, adhere a small mesh with 3M 610 tape and flatten it, squeeze out the bubbles, press statically for more than 5 minutes, keep the product still, and quickly pull up the tape side at a 90-degree angle.

[0130] The adhesion of the silver paste used to make the printed antenna should be at least 4B (less than 5% delamination of the silver layer and no cohesive failure with the silver allowed).

[0131] Adhesion of Silver Paste - Artificial Sweat

[0132] The adhesion of silver paste - artificial sweat was tested as follows: the wipe was soaked in artificial sweat at pH 4.6, placed on the silver paste sample, and then put them into a sealed bag and stored at conditions of 65±1°C / 91-95% RH for 48 hours, and then subjected to the adhesion test as above.

[0133] The adhesion of the silver paste used to make the printed antenna - artificial sweat should be at least 4B.

[0134] Adhesion of Silver Paste - Steaming

[0135] Adhesion-Cooking of Silver Paste was tested as follows: a silver paste sample was cooked for 2 hours and 30 minutes, during which time the sample could not contact the walls of the container; the sample was removed and thawed at room temperature for at least two hours; and then the adhesion test was performed as above.

[0136] The adhesion-cook of the silver paste used to make the printed antenna should be at least 4B.

[0137] RCA wear resistance of silver paste

[0138] The RCA wear resistance (175 g) of the silver paste was tested as follows: a silver paste sample was taken and a 175 g load was applied to it, and it was worn for 2000 cycles, and the appearance was inspected and the performance was tested. The RCA grinder (model: 7-IBB-CC) used was obtained from Norman tool.

[0139] The RCA abrasion resistance (175 g) of the silver paste used to make the printed antenna should not expose the substrate.

[0140] Cross section of a through hole with silver paste

[0141] The through-hole cross section of silver paste is tested as follows: fill the hole with glue and take 2pcs of silver paste product for cross-section test.

[0142] The resulting through-hole cross section of the silver paste used to make the printed antenna should not have bubbles larger than 0.5 mm in diameter in the narrowest area.

[0143] The results of the above tests on the silver paste are also listed in Table 1.

[0144] Impedance measurement of printed antennas made from silver paste

[0145] The antennas made from the silver pastes of the examples and comparative examples were prepared in the following steps:

[0146] i) applying the silver paste according to the third embodiment to the through-hole in the middle frame of the mobile phone with a dispenser, and then curing it at 80° C. for 2 hours and leaving it for 1 hour to obtain a product;

[0147] ii) applying the silver paste according to the first embodiment to the product obtained in step i) three times with a pad printer, and then curing it at 80° C. for 2 hours to obtain an Ag film with a thickness of 15 μm; and

[0148] iii) The silver paste according to the second embodiment was applied to the Ag film obtained in step ii) five times with a pad printer, and cured at 80° C. for 2 hours to obtain a printed antenna circuit.

[0149] Specific combinations of the silver pastes of the first embodiment, the second embodiment, and the third embodiment are listed in Table 2.

[0150] The impedance of the printed antenna circuit for each combination was measured by applying a 1 volt current to the antenna connector and measuring the current. The impedance was calculated using the following formula:

[0151] Impedance [Ω] = Voltage [volt] / Current [Amps]

[0152] The impedance of the antenna circuit not exceeding 1 ohm is acceptable and recorded as "pass", while the resistance greater than 1 ohm is recorded as "fail"; and the combined results are also listed in Table 2.

[0153] Table 1

[0154]

[0155]

[0156] Table 2

[0157]

[0158]

[0159] As can be seen from the above table, the silver paste according to the first embodiment has very low resistance (with a sheet resistance of less than 10mohm / square), high adhesion, and good aging characteristics, and can therefore be successfully used as a surface conductive ink; the silver paste according to the second embodiment has high wear resistance (>3000 cycles) and low resistance, and can therefore be successfully used as a touch point conductive ink; the silver paste according to the third embodiment has high strength and no bubbles, and can therefore be successfully used as a through-hole filling conductive ink. In addition, the antenna circuit prepared by the combination of the three silver pastes according to the present invention exhibits satisfactory impedance, which is suitable for electronic applications; while the natural circuit prepared by other silver paste combinations has a mismatch problem, and therefore exhibits an unsuitable impedance.

[0160] Although some preferred embodiments have been described, many modifications and variations are possible in light of the above teachings. It is therefore to be understood that the present invention may be practiced otherwise than as specifically described without departing from the scope of the appended claims.

Claims

1. A silver paste for manufacturing a printed antenna, comprising: 2 to 40 wt. % of at least one epoxy resin; 0 to 5 weight percent of at least one curing agent selected from amino resins, low temperature cationic curing agents, amine or imidazole capsule curing agents, and combinations thereof; 40 to 90 weight percent of at least one filler mixture comprising silver flakes and silver spheres; 10 to 25 wt % of at least one diluent, or 0 to 20 wt % of at least one curing accelerator; and 0 to 5 weight percent of at least one coupling agent selected from the group consisting of silane coupling agents, titanium-based coupling agents, aluminum-based coupling agents, and combinations thereof, All the above weight percentages are based on the total weight of the silver paste.

2. The silver paste according to claim 1, comprising: 2 to 20% by weight, preferably 2 to 8% by weight, more preferably 4 to 6% by weight, of at least one epoxy resin, 0 to 5 wt %, preferably 0.1 to 3 wt %, more preferably 0.2 to 2 wt % of at least one curing agent comprising an amino resin, 40 to 90 wt. %, preferably 50 to 85 wt. %, more preferably 70 to 80 wt. % of at least one filler mixture, the filler mixture comprising 1 to 40 wt. % of a tap density of more than 2 to 7 g / cm 3 Silver flakes, 35 to 88% by weight, with a tap density of 5 to 7 g / cm 3 of silver balls, and 0.08 to 0.45 wt. % of zirconium hydroxide, 5 to 25% by weight, preferably 10 to 23% by weight, more preferably 15 to 20% by weight of at least one diluent, 0 to 5 wt %, preferably 0.3 to 3 wt %, more preferably 1.0 to 2.0 wt % of at least one coupling agent selected from silane coupling agents, titanium-based coupling agents, aluminum-based coupling agents, and combinations thereof, All the above weight percentages are based on the total weight of the silver paste.

3. The silver paste according to claim 1, comprising: 2 to 20% by weight, preferably 2 to 8% by weight, more preferably 4 to 6% by weight, of at least one epoxy resin, 0.1 to 5 wt %, preferably 0.1 to 3 wt %, more preferably 0.2 to 2 wt % of at least one curing agent comprising an amino resin, 40 to 90 wt. %, preferably 50 to 85 wt. %, more preferably 70 to 80 wt. % of at least one filler mixture, the filler mixture comprising 1 to 30 wt. % of a tap density of more than 2 to 7 g / cm 3 Silver flakes, 25 to 75% by weight, with a tap density of 5 to 7 g / cm 3 silver balls, 10 to 40% by weight of wear-resistant powder having a particle size of 3.5 to 10 μm, and 0.08 to 0.45% by weight of zirconium hydroxide, 5 to 25% by weight, preferably 10 to 23% by weight, more preferably 15 to 20% by weight of at least one diluent, 0 to 5 wt %, preferably 0.3 to 3 wt %, more preferably 1.0 to 2.0 wt % of at least one coupling agent selected from silane coupling agents, titanium-based coupling agents, aluminum-based coupling agents, and combinations thereof, All the above weight percentages are based on the total weight of the silver paste.

4. The silver paste according to any one of claims 1 to 3, wherein the epoxy resin is selected from bisphenol-A resin, bisphenol-F resin and alicyclic epoxy resin; preferably selected from bisphenol-A resin and bisphenol-F resin; and more preferably bisphenol-A resin.

5. The silver paste according to any one of claims 1 to 4, wherein the amino resin is catalyzed by benzenesulfonic acid, wherein the amino resin is preferably selected from urea formaldehyde resin, melamine formaldehyde resin, and polyamide polyamine epichlorohydrin, more preferably selected from melamine formaldehyde resin; and / or the benzenesulfonic acid is used in the form of pyridinium p-toluenesulfonate.

6. The silver paste according to claim 2, wherein the filler mixture comprises 2 to 35 wt%, preferably 10 to 30 wt%, more preferably 12 to 20 wt% of the silver flakes based on the total weight of the silver paste; and / or the filler mixture comprises 40 to 80 wt%, preferably 50 to 70 wt%, more preferably 55 to 65 wt% of the silver balls based on the total weight of the silver paste; and / or the filler mixture comprises 0.1 to 0.3 wt%, preferably 0.15 to 0.25 wt% of zirconium hydroxide based on the total weight of the silver paste; and / or the particle size of the silver flakes is 5 to 8 μm; and / or the silver flakes have a particle size of 3 to 6 g / cm 3 The tap density is preferably 3.5 to 5 g / cm 3 and / or the silver spheres have a particle size of 0.2 to 5 μm, preferably 0.5 to 2 μm; and / or the silver spheres have a tap density of 5.5 to 6.5 g / cm 3 .

7. The silver paste according to claim 3, wherein the filler mixture comprises 2 to 25 wt. %, preferably 3 to 10 wt. %, more preferably 4 to 8 wt. % of the silver flakes, based on the total weight of the silver paste; and / or the filler mixture comprises 30 to 70 wt. %, preferably 40 to 60 wt. %, more preferably 45 to 55 wt. % of the silver balls, based on the total weight of the silver paste; and / or the filler mixture comprises 12 to 30 wt. %, preferably 18 to 25 wt. % of the wear-resistant powder, based on the total weight of the silver paste; and / or the filler mixture comprises 0.1 to 0.3 wt. %, preferably 0.15 to 0.25 wt. % of zirconium hydroxide, based on the total weight of the silver paste.

8. The silver paste according to claim 3 or 7, wherein the particle size of the silver flakes is 5 to 8 μm; and / or the silver flakes have a particle size of 3 to 6 g / cm 3 The tap density is preferably 3.5 to 5 g / cm 3 and / or the silver spheres have a particle size of 0.2 to 5 μm, preferably 0.5 to 2 μm; and / or the silver spheres have a tap density of 5.5 to 6.5 g / cm 3 ; and / or the wear-resistant powder is selected from silicon powder, zirconium oxide powder, aluminum oxide powder and alloy powder, wherein the alloy powder is preferably selected from iron-nickel alloy powder and iron-manganese alloy powder, more preferably iron-nickel alloy powder; and / or the alloy powder has a particle size of 4 to 8 μm, preferably 4.5 to 7 μm.

9. The silver paste according to any one of claims 1 to 8, wherein the diluent is selected from ketones and esters; preferably selected from isophorone, acetylacetone, cyclohexyl acetate, ethylene glycol butyl ether acetate, and propylene glycol methyl ether acetate; and is a mixture of isophorone, acetylacetone, cyclohexyl acetate, ethylene glycol butyl ether acetate, and propylene glycol methyl ether acetate.

10. The silver paste according to claim 1, comprising: 10 to 40% by weight, preferably 11 to 30% by weight, more preferably 12 to 20% by weight of at least one epoxy resin, 0.1 to 3 wt %, preferably 0.2 to 2 wt %, more preferably 0.3 to 1 wt % of at least one curing agent, the curing agent comprising a low temperature cationic curing agent, or an amine or imidazole capsule curing agent, 50 to 90 wt. %, preferably 60 to 88 wt. %, more preferably 75 to 85 wt. % of at least one filler mixture, the filler mixture comprising 45 to 89 wt. % of a tap density of more than 2 to 7 g / cm 3 Silver flakes, and 1 to 45 wt % of a tap density of 5 to 7 g / cm 3 The silver ball, 1 to 20% by weight, preferably 2 to 15% by weight, more preferably 3 to 10% by weight of at least one curing accelerator, 0 to 5 wt %, preferably 0.3 to 3 wt %, more preferably 1.0 to 2.0 wt % of at least one coupling agent selected from silane coupling agents, titanium-based coupling agents, aluminum-based coupling agents, and combinations thereof, All the above weight percentages are based on the total weight of the silver paste.

11. The silver paste according to claim 10, wherein the epoxy resin is selected from bisphenol-A resin, bisphenol-F resin and alicyclic epoxy resin; preferably selected from bisphenol-F resin and alicyclic epoxy resin; and more preferably a combination of bisphenol-F resin and alicyclic epoxy resin.

12. The silver paste according to claim 10 or 11, wherein the low-temperature cationic curing agent is cured at a temperature of 60 to 90°C, preferably at a temperature of 70 to 80°C; and / or the low-temperature cationic curing agent is hexafluoroantimonate and / or hexafluorophosphate, and preferably hexafluoroantimonate; and / or the amine or imidazole capsule curing agent is an imidazole capsule curing agent.

13. The silver paste according to any one of claims 10 to 12, wherein the filler mixture comprises 50 to 85 wt%, preferably 60 to 80 wt%, more preferably 65 to 75 wt% of the silver flakes based on the total weight of the silver paste; and / or the filler mixture comprises 2 to 35 wt%, preferably 5 to 20 wt%, more preferably 8 to 15 wt% of the silver spheres based on the total weight of the silver paste; and / or the particle size of the silver flakes is 5 to 20 μm; and / or the particle size of the silver spheres is 5 to 20 μm; and / or the silver flakes have a particle size of 3 to 6 g / cm 3 The tap density is preferably 3.5 to 5 g / cm 3 and / or the tap density of the silver ball is 5.5 to 6.5 g / cm 3 .

14. The silver paste according to any one of claims 10 to 13, wherein the curing accelerator is selected from oxetanes, and preferably (3-ethyl-3-oxetanyl)methanol.

15. A kit of parts for preparing a printed antenna for an electronic device, comprising individually packaged a first container containing a silver paste according to any one of claims 2, 4 to 6 and 9, a second container containing a silver paste according to any one of claims 3 to 5 and 7 to 9, and - A third container, wherein the third container contains the silver paste according to any one of claims 10 to 14.

16. Use of the silver paste according to any one of claims 10 to 14 as a through-hole filling ink for conductive connection between surface silver paste and touch point silver paste, wherein the conductive connection is preferably a conductive connection between the silver paste according to any one of claims 2, 4 to 6 and 9 and the silver paste according to any one of claims 3 to 5 and 7 to 9.

17. A method for preparing a printed antenna circuit comprising the steps of: i) applying the silver paste according to any one of claims 10 to 14 to the through-hole in the middle frame of the mobile phone with a dispensing machine, and then curing it at 80 to 90° C. for 0.5 to 2 hours, preferably 0.8 to 1.5 hours, more preferably about 1 hour, and leaving it for 0.5 to 2 hours to obtain a product; ii) applying the silver paste according to any one of claims 2, 4 to 6 and 9 to the product obtained in step i) three times with a pad printer, and then curing it at 80 to 90° C. for 0.5 to 2 hours, preferably 0.8 to 1.5 hours, more preferably about 1 hour, to obtain an Ag film with a thickness of 10 to 20 μm, preferably about 15 μm; and iii) applying the silver paste according to any one of claims 3 to 5 and 7 to 9 to the Ag film obtained in step ii) five times using a pad printer, and curing it at 80 to 90° C. for 1 to 3 hours, preferably 1.5 to 2.5 hours, more preferably about 2 hours to obtain a printed antenna circuit.

18. The method according to claim 17, wherein the middle frame of the mobile phone is made of PC, LPA, aluminum alloy, ceramic, glass and / or magnesium alloy.

19. A printed antenna for an electronic device, obtained using the silver paste according to any one of claims 1 to 14, preferably obtained using the silver paste according to any one of claims 2, 4 to 6 and 9, the silver paste according to any one of claims 3 to 5 and 7 to 9, and / or the silver paste according to any one of claims 10 to 14, and more preferably obtained using the set of components according to claim 15.

20. Electronic device comprising the printed antenna according to claim 19.